Biogenic Phytochemicals Modulating Obesity: From Molecular Mechanism to Preventive and Therapeutic Approaches. (27th March 2022) - Kumar, Vikram; Singh, Desh Deepak; Lakhawat, Sudarshan Singh; Yasmeen, Nusrath; Pandey, Aishwarya; Singla, Rajeev K.
Abstract : The incidence of obesity and over bodyweight is emerging as a major health concern. Obesity is a complex metabolic disease with multiple pathophysiological clinical conditions as comorbidities are associated with obesity such as diabetes, hypertension, cardiovascular disorders, sleep apnea, osteoarthritis, some cancers, and inflammation-based clinical conditions. In obese individuals, adipocyte cells increased the expression of leptin, angiotensin, adipocytokines, plasminogen activators, and C-reactive protein. Currently, options for treatment and lifestyle behaviors interventions are limited, and keeping a healthy lifestyle is challenging. Various types of phytochemicals have been investigated for antiobesity potential. Here, we discuss pathophysiology and signaling pathways in obesity, epigenetic regulations, regulatory mechanism, functional ingredients in natural antiobesity products, and therapeutic application of phytochemicals in obesity.